Análisis de la prisión preventiva como medida cautelar de carácter excepcional; y, la aplicación de las reglas establecidas en el artículo 534 del código orgánico integral penal. - Marcillo Pauta, Andrea Briggette (2022)
The following research is elaborated with the purpose of analyzing pre-trial detention as a precautionary measure of an exceptional personal nature, which will proceed when the other precautionary measures are insufficient to ensure the objectives of the process, which are summarized in the verification according to law of the existence of the offense and the criminal liability of the defendant. The correct implementation of preventive imprisonment is a topic of novelty and permanent discussion due to the abuse of this measure by Ius-penalists. Consequently, the plenary of the National Court of Justice (CNJ) states that preventive detention is an exceptional precautionary measure, which must be requested and ordered in accordance with the circumstances of each specific case, under ultima ratio criteria (Resolution, 2021 N° 14). By default, pretrial detention is the most coercive measure and consequently ought to be applied under criteria of ultima ratio, thus, it has to be subsidiary. Therefore, it must be applied or assigned by the justice operators when it is considered that no other personal precautionary measure is useful and effective to ensure the appearance of the defendant. Hence, enforce protective measures to safeguard the rights of individuals by avoiding the violation of the right to work, education, health, presumption of innocence, personal liberty, due process of law. Consequently, to avoid the crisis of the penitentiary system that are the prison overcrowding, so that one out of three inmates are people in pretrial detention, without highlighting the people who are without convictions saturating the policy inside the prisons and the living conditions of people deprived of liberty under this precautionary measure. Considering that our legislation is a democratic, constitutional state of rights and justice. Proclaiming the intervening Laws and Codes such as: The International Treaties, The Constitution of the Republic, The Organic Integral Penal Code, The Inter-American Commission of Human Rights, The Universal Declaration of Human Rights, The American Convention of Human Rights.